Impact of compression on velocity of venous and arterial main blood flow and cutaneous microcirculation of the lower extremity - V. I. Rusin; F. M. Pavuk; V. Ya. Fedusyak (Клінічна хірургія)
Objective. To study the impact of compression on velocity of venous and arterial main blood flow of the lower extremity, as well as cutaneous microcirculation in the back part of the foot in healthy individuals and patients with decompensated forms of varicose disease and postthrombophlebitis syndrome.